Curcumin reduces renal damage associated with rhabdomyolysis by decreasing ferroptosis‐mediated cell death. Issue 8 (29th April 2019) - Guerrero‐Hue, Melania; García‐Caballero, Cristina; Palomino‐Antolín, Alejandra; Rubio‐Navarro, Alfonso; Vázquez‐Carballo, Cristina; Herencia, Carmen; Martín‐Sanchez, Diego; Farré‐Alins, Víctor; Egea, Javier; Cannata, Pablo; Praga, Manuel; Ortiz, Alberto; et al.
ABSTRACT: Acute kidney injury is a common complication of rhabdomyolysis. A better understanding of this syndrome may be useful to identify novel therapeutic targets because there is no specific treatment so far. Ferroptosis is an iron‐dependent form of regulated nonapoptotic cell death that is involved in renal injury. In this study, we investigated whether ferroptosis is associated with rhabdomyolysis‐mediated renal damage, and we studied the therapeutic effect of curcumin, a powerful antioxidant with renoprotective properties. Induction of rhabdomyolysis in mice increased serum creatinine levels, endothelial damage, inflammatory chemokines, and cytokine expression, alteration of redox balance (increased lipid peroxidation and decreased antioxidant defenses), and tubular cell death. Treatment with curcumin initiated before or after rhabdomyolysis induction ameliorated all these pathologic and molecular alterations. Although apoptosis or receptor‐interacting protein kinase (RIPK)3‐mediated necroptosis were activated in rhabdomyolysis, our results suggest a key role of ferroptosis. Thus, treatment with ferrostatin 1, a ferroptosis inhibitor, improved renal function in glycerol‐injected mice, whereas no beneficial effects were observed with the pan‐caspase inhibitor carbobenzoxy‐valyl‐alanyl‐aspartyl‐( O ‐methyl)‐fluoromethylketone or in RIPK3‐deficient mice. In cultured renal tubular cells, myoglobin (Mb) induced ferroptosis‐sensitive cell death that was also inhibited by curcumin. Mechanistic in vitro studies showed that curcumin reduced Mb‐mediated inflammation and oxidative stress by inhibiting the TLR4/NF‐κB axis and activating the cytoprotective enzyme heme oxygenase 1. Our findings are the first to demonstrate the involvement of ferroptosis in rhabdomyolysis‐associated renal damage and its sensitivity to curcumin treatment. Therefore, curcumin may be a potential therapeutic approach for patients with this syndrome.—Guerrero‐Hue, M., García‐Caballero, C., Palomino‐Antolín, A., Rubio‐Navarro, A., Vázquez‐Carballo, C., Herencia, C., Martín‐Sanchez, D., Farré‐Alins, V., Egea, J., Cannata, P., Praga, M., Ortiz, A., Egido, J., Sanz, A. B., Moreno, J. A. Curcumin reduces renal damage associated with rhabdomyolysis by decreasing ferroptosis‐mediated cell death. FASEB J. 33, 8961–8975 (2019). www.fasebj.org